Capacitor-inspired high-performance and durable moist-electric generator. Issue 11 (3rd October 2022) - Sun, Zhaoyang; Wen, Xian; Wang, Liming; Yu, Jianyong; Qin, Xiaohong
Abstract : Harvesting clean and sustainable energy from moisture has emerged as a promising technology to break the paradigm of traditional energy generation by utilizing fossil fuels. Abstract : Harvesting clean and sustainable energy from moisture has emerged as a promising technology to break the paradigm of traditional energy generation by utilizing fossil fuels. However, the current design principles for moist-electric generators (MEGs) are mainly based on constructing a conformation gradient or water gradient in materials, or building electrokinetic streaming potential through a nanoporous structure, which is unfavorable for realizing spontaneous sustained electricity generation. Herein, inspired by electric double-layer capacitors, we propose a novel strategy to design a moist-electric generator via applying a pair of differently charged electrodes and an electrolyte-loaded nanofiber film. The assembled generator simultaneously achieved a sustained voltage and current output of 0.7 V and 3 μA over 120 h without obvious weakening while remaining sensitive to giving a moist response in a wide humidity range (35–95%), reaching the highest level among the existing moist-electric generators. Remarkably, the ion-diffusion force of the capacitor-inspired moist-electric generator (CMEG) originated from the adsorption of released ions by the charged electrode, which is different from the previously reported devices. This new type of generator can directly power electronics and successfully show the practical use in respiration monitors and touch sensing. This work provides new insights for designing future moist-electric generators, further facilitating the development of green and sustainable power generation.